(3GdESJKeGQ aj GdSfOGJ hGdCSge (B/s - (3hGjJ, Lhfs ((3GdbGgQI(B: s (3OGQ GdaGQhb(B, s, 2006)
(3GdOGaY hQGA TQGA GdCSge(B-(3GdJYQja HGdCSge(B-(3GdYhGed GdJj JDKQ Ydi CSYGQ GdCSge(B-(3GdeYGedGJ GdNGUI HGdCSge(B-(3GdESJQGJjLjGJ GdNGUI HGdHhQUI(B-(3GdESJKeGQ aj Mbhb GdJLGQI(B-(3GdSfOGJ hGdSfOGJ GdeYfhfI hGdhOGFY PGJ GdaGFOI(B-(3SJI MGdGJ OQGSjIs
Keywords: (3GdESJKeGQs; (3GdSfOGJs; (3GdeYGedGJs; (3TQGA GdCSges